Microsoft 70-243 : administering and deploying SCCM 2012. - Safari eBooks ([Place of publication not identified] : iCollege, 2017)
"This course prepares you to accomplish the following in order to prepare for the 70-243 exam: Design and plan System Center Configuration Manager infrastructure, Manage operating system deployment (OSD), Deploy applications and software updates, Manage compliance settings, Manage sites, Manage clients, Manage inventory, Manage reports and queries."--Resource description page.
Title from resource description page (Safari, viewed October 26, 2017).
Keywords: Microsoft System center configuration manager; Computer networks; Electronic books